Laparoscopic fundoplication in children with ventriculo-peritoneal shunts - Kubiak, Rainer; Skerritt, Clare; Grant, Hugh W. (Journal of laparoendoscopic & advanced surgical techniques, 2012)
Children with ventriculo-peritoneal (V-P) shunts have a significant risk of morbidity and mortality from infections. Many of these patients have other co-morbidities and may require subsequent abdominal surgery, including fundoplication with or without gastrostomy placement. The aim of our study was to assess the outcomes of laparoscopic fundoplication in children with a V-P shunt in situ.